15.21 Next-generation sequencing in charcot-marie-tooth disease: opportunities and challenges. Issue 12 (14th November 2019) - Pipis, Menelaos; Rossor, Alexander M; Doherty, Carolynne M; Laura, Matilde; Reilly, Mary M
Abstract : Charcot-Marie-Tooth (CMT) disease and related disorders encompass a phenotypically and genetically heterogeneous group of disorders. Our diagnostic approach to CMT has been revolutionised by the advent and use of next-generation sequencing (NGS) technologies with applications in CMT gene panels, whole exome and whole genome sequencing, mitochondrial sequencing and high-throughput transcriptome sequencing. We present the up to date evidence pertaining to the application of these technologies in CMT diagnostics and also discuss what challenges they bring in relation to variant interpretation. Phenotypic, genetic and bioinformatic evidence should be used to overcome these challenges, and we discuss how setting a maximum credible population allele frequency for pathogenic variants in dominant and recessive CMT genes is crucial in filtering efficiently NGS-derived variants. Whole genome sequencing as a single molecular genetic test is very appealing and, in the context of the 100, 000 Genome Project, we suggest how its application into CMT clinical practice can happen with a balance between improved diagnostic yield and burden of variant analysis.